2017
DOI: 10.1002/art.39965
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Activation of Transforming Growth Factor β–Activated Kinase 1 in Chondrocytes by Phosphorylation and K63‐Linked Polyubiquitination Upon Injury to Animal Articular Cartilage

Abstract: ObjectiveMechanical injury to cartilage predisposes to osteoarthritis (OA). Wounding of the articular cartilage surface causes rapid activation of MAP kinases and NF‐κB, mimicking the response to inflammatory cytokines. This study was undertaken to identify the upstream signaling mechanisms involved.MethodsCartilage was injured by dissecting it from the articular surface of porcine metacarpophalangeal (MCP) joints or by avulsing murine proximal femoral epiphyses. Protein phosphorylation was assayed by Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 46 publications
1
44
0
Order By: Relevance
“…However, both YAP and TAK1 have been implicated in response to mechanical stimuli. TAK1 is activated upon cartilage injury 48 and YAP activity is inhibited upon mechanical stress 33 . It seems that the trigger on TAK1/YAP action is multifactorial in OA development, in which both mechanical stress and inflammatory stimuli will result in similar actions on TAK/YAP.…”
Section: Discussionmentioning
confidence: 99%
“…However, both YAP and TAK1 have been implicated in response to mechanical stimuli. TAK1 is activated upon cartilage injury 48 and YAP activity is inhibited upon mechanical stress 33 . It seems that the trigger on TAK1/YAP action is multifactorial in OA development, in which both mechanical stress and inflammatory stimuli will result in similar actions on TAK/YAP.…”
Section: Discussionmentioning
confidence: 99%
“…; Ismail et al . ). The receptor proximal mechanism of activation for most of these remains unknown.…”
Section: Articular Cartilage Is Adapted To Withstand Mechanical Stressmentioning
confidence: 97%
“…The upstream activator of TAK1 remains elusive and does not appear to be mediated by a soluble factor (Ismail et al . ). Exceeding the injury threshold could occur either when the mechanical load is increased, or when the load is moderate but the joint has lost its mechanoprotective mechanisms.…”
Section: Articular Cartilage Is Adapted To Withstand Mechanical Stressmentioning
confidence: 97%
“…Osteoarthritis is a mechanically driven disease. This notion is compellingly described in the epidemiological literature 6 and confirmed in basic science studies, which have shown the highly mechanosensitive nature of joint tissues, 7 , 8 , 9 , 10 , 11 , 12 the activation of inflammatory signalling by mechanical injury, 12 , 13 the dependence on mechanics in preclinical osteoarthritis, 14 , 15 and the involvement of mechanosensing mechanisms in in-vivo pathogenesis. 16 , 17 Several other important causal factors—such as obesity, age, and genetics—affect the ability of joint tissues to withstand mechanical stress over a lifetime and affect the ability to repair damaged tissues.…”
Section: Introductionmentioning
confidence: 81%